Media framing and attitudinal bias toward the elderly: A Comparative study of US and Chinese media discourse - Hong Meng; Azianura Hani Binti Shaari; Lay Shi Ng (Environment and Social Psychology, 2025)
Against the backdrop of global ageing, the portrayal of the elderly in the media reflects societal attitudes towards this senior group and influences public perceptions of ageing. This study focuses on the term “elderly” and employs quantitative corpus-assisted approach, qualitative framing analysis, and semantic prosody analysis to compare how Chinese and American mainstream news media construct older adults. The corpus was sourced from China Daily, South China Morning Post, The Washington Post, and The New York Times throughout the entire year of 2023. A total of 359 concordance lines from China news media and 22 from American news media were examined for media framing and semantic prosody of the term “elderly”. The results showed that Chinese outlets more frequently employed “elderly” to refer to older adults, predominantly constructed them within the frame of institutional support, and tended to exhibit positive attitudes. In contrast, American media seldom utilized “elderly” and framed older people within negative societal contexts linked to challenges and difficulties. Specifically, 59.09% of the mentions in American contexts highlighted problematic aspects, whereas in China, 44.29% of the references depicted the elderly as beneficiaries of diverse institutional supports and volunteer efforts. This US-China comparative study of the term “elderly” revealed different dominant media frames and overall attitudes between China and American news outlets, which guide media professionals to rethink the power of language used to describe the elderly.